Analysis of crack initiation and propagation in Thermal Barrier Coatings using SEM-Based geometrical model with extended finite element method. Issue 23 (1st December 2021) - Abdelgawad, Ahmed; Al-Athel, Khaled; Albinmousa, Jafar
Abstract: Thermal Barrier Coatings (TBC) are widely used to protect the metallic components that operate at harsh conditions of elevated temperatures and oxidizing environments. Thermally grown oxide (TGO) causes cracks formation in the top coat (TC) that may lead to spallation failure of TBC. This work investigates effect of pores and TGO thickness on crack initiation and propagation due to thermal mismatch between TBC layers. Image processing is used to convert an SEM image, including pores, into a finite element (FE) model. An FE model using XFEM implemented in ABAQUS was developed to investigate crack initiation and propagation for various TGO thicknesses considering the effect of plastic deformation of BC, TGO and substrate. Results show that presence of pores changes the critical sites for crack initiation from the TC/TGO interface to be around the pores within the TC. Crack initiation temperatures and crack lengths were found to be affected with both TGO thickness and pores.